Trying to Make It: The Enterprises, Gangs, and People of the American Drug Trade - Gundur, Rajeev Vishwanath (Cornell University Press, 2022)
Trying To Make It -- Contents -- Preface -- Acknowledgments -- List of Abbreviations -- 1. Home -- 2. The Southern Border -- 3. Immigration Court -- 4. The Santa Fe Street Bridge -- 5. Business as Usual -- 6. Father and Son -- 7. La Carrucha -- 8. Violence -- 9. The Street -- 10. The Oasis -- 11. Gangs of the Valley -- 12. Adelita and Calista -- 13. A Fear of Corners -- 14. Connections -- 15. The City by the Lake -- 16. Gangland -- 17. Catching Cases -- 18. Logistics -- 19. Responding to the Drug Trade -- 20. Trainspotting -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z.